An interpretive review of selective sweep studies in Bos taurus cattle populations: identification of unique and shared selection signals across breeds - Gutiérrez-Gil, Beatriz; Arranz, Juan J.; Wiener, Pamela (Frontiers in Genetics, 2015)
This review compiles the results of 21 genomic studies of European Bos taurus breeds and thus provides a general picture of the selection signatures in taurine cattle identified by genome-wide selection-mapping scans. By performing a comprehensive summary of the results reported in the literature, we compiled a list of 1,049 selection sweeps described across 37 cattle breeds (17 beef breeds, 14 dairy breeds and 6 dual-purpose breeds), and four different beef-vs-dairy comparisons, which we subsequently grouped into core selective sweep (CSS) regions, defined as consecutive signals within 1 Mb of each other. We defined a total of 409 CSSs across the 29 bovine autosomes, 232 (57%) of which were associated with a single-breed (Single-breed CSSs), 134 CSSs (33%) were associated with a limited number of breeds (Two-to-four-breed CSSs) and 39 CSSs (9%) were associated with five or more breeds (Multi-breed CSSs). For each CSS, we performed a candidate gene survey that identified 291 genes within the CSS intervals (from the total list of 5,183 BioMart-extracted genes) linked to dairy and meat production, stature and coat colour traits. A complementary functional enrichment analysis of the CSS positional candidates highlighted other genes related to pathways underlying behaviour, immune response and reproductive traits. The Single-breed CSSs revealed an over-representation of genes related to dairy and beef production, this was further supported by over-representation of production-related pathway terms in these regions based on a functional enrichment analysis. Overall, this review provides a comparative map of the selection sweeps reported in European cattle breeds and presents for the first time a characterization of the selection sweeps that are found in individual breeds. Based on their uniqueness, these breed-specific signals could be considered as "divergence signals", which may be useful in characterising and protecting livestock genetic diversity.